Efek Kinesiotaping dan Latihan Penguatan Otot Kuadriseps terhadap Aktivitas Otot Rektus Femoris, Vastus Medialis Oblik dan Vastus Lateralis, Intensitas Nyeri dan Status Fungsional Penderita Osteoartritis Lutut: Uji Acak Terkontrol - Novaria Puspita; Tertianto Prabowo; Irma Ruslina Defi (Majalah Kedokteran Indonesia, 2019)
Aim: The aim of this study was to determine the effects of Kinesiotaping (KT) and quadriceps muscle strengthening exercises on muscle activity of Rectus Femoris (RF), Vastus Medial Oblique (VMO) and Vastus Lateral (VL), pain intensity, and functional status of patients with knee OA.Method: This study used a double blind randomized controlled trial design. Twenty-six women with knee OA were randomly divided into treatment and control groups. The treatment group was given KT on three quadriceps muscles and quadriceps strengthening exercise, the control group received “sham taping” and quadriceps strengthening exercise. Measured muscle activity with surface electromyography (sEMG), Numerical Rating Scale (NRS) and Aggregated Locomotor Function (ALF) scale before and after treatment 4, 6, and 8 weeks.Result: There were significant difference in rectus femoris (RF) muscle activity (p = 0.033) between the treatment and control groups at week 8 but there were no significant differences (p greater than 0.05) between group for the vastus medialis oblique (VMO) and vastus lateralis (VL) muscle activiy, NRS and ALF at weeks 4,6 and 8.Conclusion: KT plus quadriceps strengthening exercise does not offer advantages for improvement of pain, functional status, VMO and VL muscle activity compared with “sham” taping plus quadriceps strengthening in knee OA, other than an improvement of RF muscle activity.